The Effectiveness of Using Swipoa Learning Media on the Basic Arithmetic on the Results of Learning of Third Grade Students at Lalangon I Elementary School: Efektivitas Penggunaan Media Pembelajaran Swipoa Terhadap Hasil Belajar Aritmatika Dasar Siswa Kelas III SDN Lalangon I - Naimah, Putri Hafiyatun Naimah; Sari, Tita Tanjung; Kadarisman (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study was conducted due to the low learning outcomes in basic arithmetic among third-grade students at Lalangon I elementary school. The research aimed to determine the effectiveness of using Swipoa learning media on students' basic arithmetic achievement. A quantitative approach was employed, utilizing a true experimental design with a pretest-posttest control group. Data collection involved test instruments comprising pretest and posttest questions. A simple random sampling technique was used to select 49 of third-grade students from Lalangon I elementary school. Data analysis included prerequisite tests and hypothesis testing. The normality test results indicated that the pretest scores in the control class (0.972 > 0.05) and the experimental class (0.215 > 0.05) were normally distributed. Similarly, the posttest scores in the control class (0.685 > 0.05) and the experimental class (0.537 > 0.05) also followed a normal distribution. Homogeneity tests showed that the pretest (0.877 > 0.05) and posttest (0.408 > 0.05) scores came from populations with equal variances. The t-test analysis revealed a calculated t-value (tₕ) of 8.5, which is greater than the critical t-value (tₜ) of 2.011, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). The n-gain score was 67%, indicating an effective criterion. Therefore, it can be concluded that the Swipoa learning media is effective in enhancing the basic arithmetic learning outcomes of third-grade students at Lalangon I elementary school.